2019
DOI: 10.1007/s10856-019-6221-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gold nanoparticles shape on their cytotoxicity against human osteoblast and osteosarcoma in in vitro model. Evaluation of the safety of use and anti-cancer potential

Abstract: Due to development of nanotechnology and gold nanoparticles (AuNPs) increasing use in different areas of medicine, especially in oncology, better understanding of their potential cytotoxicity is necessary to protect patients safety. Shape and size of AuNPs is an important modulator of their cytotoxicity. Therefore, we investigated the cytotoxicity of AuNPs rods (≈39 nm length, 18 nm width), AuNPs stars (≈ 215 nm) and AuNPs spheres (≈ 6.3 nm) against human fetal osteoblast (hFOB 1.19), osteosarcoma (143B, MG63)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(96 citation statements)
references
References 66 publications
3
84
1
Order By: Relevance
“…The same previously discussed morphological characteristics affect the anti-tumoral potential of nanoparticles. Literature data suggest that nanospheres possess the weakest cytotoxic potential (in the case of Ag and Au NPs), with the most promising morphologies being the nanowires (Ag NPs) [130] and the nanostars (Au NPs) [131]. El-Hawary et al [84] studied the potential of Ag NPs that were obtained by using two cultivars (with similar compositions) of Jasminum sambac L. The nanoparticles with smaller dimensions (8.83 nm) exhibited a higher cytotoxic potential against MCF-7 cells and human bladder carcinoma cells (5637) ( Table 3) and lower toxicity towards immortal keratinocyte cells (HaCaT) ( Table 4), as compared with the higher dimension NPs.…”
Section: Recent Findings In the Morphology-properties Correlationmentioning
confidence: 99%
“…The same previously discussed morphological characteristics affect the anti-tumoral potential of nanoparticles. Literature data suggest that nanospheres possess the weakest cytotoxic potential (in the case of Ag and Au NPs), with the most promising morphologies being the nanowires (Ag NPs) [130] and the nanostars (Au NPs) [131]. El-Hawary et al [84] studied the potential of Ag NPs that were obtained by using two cultivars (with similar compositions) of Jasminum sambac L. The nanoparticles with smaller dimensions (8.83 nm) exhibited a higher cytotoxic potential against MCF-7 cells and human bladder carcinoma cells (5637) ( Table 3) and lower toxicity towards immortal keratinocyte cells (HaCaT) ( Table 4), as compared with the higher dimension NPs.…”
Section: Recent Findings In the Morphology-properties Correlationmentioning
confidence: 99%
“…However, a very slightly negative slope was found which represents very less cytotoxic at high concentration of nanoparticles. The previous study has used very few concentration gold nanoparticles for cytotoxicity analysis [33,34]. We have found that cytotoxicity is very less with a high concentration of nanoparticles.…”
Section: Cytotoxicity Assaysmentioning
confidence: 81%
“…Interestingly, other studies suggested that the anticancer activity of AuNPs is shape dependent. 143b and MG63 osteosarcoma cells were sensitive to AuNPs rods and stars but not to AuNPs spheres [20]. AuNPs are not the only NPs with anticancer activity.…”
Section: Nanoparticles Cytotoxicity To Osteosarcoma Cellsmentioning
confidence: 92%